Developing the Lonergan Legacy : Historical, Theoretical, and Existential Issues - Crowe, Frederick E. (Book collections on Project MUSE., 2004)
Comprising twenty papers, including six never before published, this long-awaited work spans the fifty-year career of noted theologian Frederick E. Crowe, a scholar who has devoted himself to studying, expounding, and making available the writings of Bernard Lonergan, the well-known Canadian Jesuit philosopher and theologian who died in 1984. The publication of these papers, compiled by Michael Vertin, is a tribute both to their subject and to their author. Developing the Lonergan Legacy both recounts the history of Lonergan's work in philosophy and theology, and offers significant theoretical and existential developments of that work. Divided into two sections 'studies, ' which examines the historical context of Lonergan and his writings, and 'essays, ' which applies Lonergan's work in different directions the essays in this volume are motivated by Crowe's deep concern for the concrete intellectual, moral, and religious welfare of his readers, of all those whom his readers might influence, and ultimately of the entire human community. Vertin's meticulous editing and thoughtful sequencing only add to the uniquely spiritual character of Crowe's works.